Lipoprotein Abnormalities Associated with Mild Impairment of Kidney Function in the Multi-Ethnic Study of Atherosclerosis - de Boer, Ian H. (American Society of Nephrology, 2008)
Background and objectives: Impaired kidney function is associated with increased risk for cardiovascular disease and may progress over time to end-stage renal disease. Abnormal lipoprotein metabolism has been implicated as a possible cause of these complications, but lipoproteins have not been described at the earliest stages of kidney disease. Design, setting, participants, & measurements: This study examined cross-sectional associations of serum cystatin C with conventional lipid measurements and detailed nuclear magnetic resonance lipoprotein measurements in the community-based Multi-Ethnic Study of Atherosclerosis. A total of 5109 participants with estimated glomerular filtration rate ≥60 ml/min per 1.73 m(2) were included in analyses. Results: Adjusting for age, gender, race/ethnicity, diabetes, impaired fasting glucose, BP, smoking, medications, body mass index, and albuminuria, greater cystatin C concentrations were associated with progressively unfavorable lipid and lipoprotein concentrations, including greater triglyceride concentration (+22 mg/dl, comparing fifth versus first quintiles of cystatin C) and lesser high-density lipoprotein cholesterol concentration (−7 mg/dl) but not with low-density lipoprotein cholesterol measured using conventional methods. When low-density lipoprotein particle subclasses were examined in more detail using nuclear magnetic resonance, greater cystatin C was associated with greater concentrations of atherogenic small low-density lipoprotein particles (+63 nmol/L) and intermediate-density lipoprotein particles (+6 nmol/L) and with a decrease in mean low-density lipoprotein particle size. Conclusions: Lipoprotein abnormalities are present with milder degrees of renal impairment than previously recognized, and abnormalities in low-density lipoprotein particle distribution may not be appreciated using conventional lipid measurements. These abnormalities may contribute to kidney disease progression and/or cardiovascular disease.